Ionic Liquid Electrolytes for Safer Lithium Batteries: I. Investigation Around Optimal Formulation. (30th August 2016) - Moreno, Margherita; Simonetti, Elisabetta; Appetecchi, Giovanni Battista; Carewska, Maria; Montanino, Maria; Kim, Guk-Tae; Loeffler, Nicholas; Passerini, Stefano
Abstract : In this paper we report on the investigation of ionic liquid-based electrolytes with enhanced characteristics. In particular, we have studied ternary mixtures based on the lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) salt and two ionic liquids sharing the same cation ( N -methyl- N -propyl pyrrolidinium, PYR13 ), but different anions, bis(trifluoromethanesulfonyl)imide (TFSI) and bis(fluorosulfonyl)imide (FSI). The LiTFSI-PYR13 TFSI-PYR13 FSI mixtures exhibit better ion transport properties (about 10 -3 S cm -1 at -20 °C) with respect to similar ionic liquid electrolytes till reported in literature. An electrochemical stability window of 5 V is observed in carbon working electrodes.